2016
DOI: 10.1124/jpet.116.232694
|View full text |Cite
|
Sign up to set email alerts
|

 -Lapachone Induces NAD(P)H:Quinone Oxidoreductase-1- and Oxidative Stress-Dependent Heat Shock Protein 90 Cleavage and Inhibits Tumor Growth and Angiogenesis

Abstract: b-Lapachone [b-lap; 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione] is a novel anticancer drug currently under investigation in phase I/II clinical trials. However, the mechanism underlying its clinical efficacy remains unclear. In this study, we found that b-lap provoked the cleavage of heat shock protein 90 (Hsp90) in NAD(P)H:quinone oxidoreductase-1 (NQO1)-expressing lung and prostate cancer cells as well as in primary human umbilical vein endothelial cells (HUVECs). These actions of b-lap were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 44 publications
(61 reference statements)
0
24
0
Order By: Relevance
“…As human fibroblasts WI-38 express NQO1 but are not able to develop the NQO1-mediated redox cycle that could lead to HSP90 (Heat Shock Protein) inhibition upon β-Lapachone induction [44], it was presumed that these cells may have a genotype NQO1*1/*2. When we worked with WI-38 [45], the DNA was preserved from an early passage and kept frozen at −20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…As human fibroblasts WI-38 express NQO1 but are not able to develop the NQO1-mediated redox cycle that could lead to HSP90 (Heat Shock Protein) inhibition upon β-Lapachone induction [44], it was presumed that these cells may have a genotype NQO1*1/*2. When we worked with WI-38 [45], the DNA was preserved from an early passage and kept frozen at −20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…PARP1 hyperactivation by DNA damage is considered to result in depletion of cellular NAD + and ATP levels (Bai et al, ). Many studies have revealed that the beneficial properties of β‐lap on multiple metabolic syndromes and cisplatin‐mediated ototoxicity/nephrotoxicity were mediated by increased intracellular NAD + levels and SIRT1 activation by inhibiting PARP hyperactivation (Kim, Oh, Shen, et al, ; Wu et al, ). Because PARP1 and SIRTs compete with the same cellular NAD + pool, PARP1 activation has a significant effect on SIRTs activity by decreasing NAD + bioavailability (Bai et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al . also reported that β-lap effectively inhibited angiogenesis by suppressing tube formation and the invasion of HUVECs in vitro , and suppressed the growth and angiogenesis of human lung cancer xenografts in nude mice 18 . Additionally, numerous lines suggested that the mechanism for which β-lap had become a promising candidate for cancer therapy was dependent on the enzymatic activity of the two-electron oxidoreductase, NQO1 19, 20 .…”
Section: Introductionmentioning
confidence: 89%